Strategi Pengembangan Industri Halal Di Indonesia - Hairullah Efendi; Rahmawati Rahmawati; Rio Panji Saputra; Zafia Sarina Yoly (EL-EMIR Institute, 2026)
The halal industry is a strategic sector with significant potential to support national economic growth, particularly in Indonesia, the country with the largest Muslim population in the world. As public awareness of halal products increases, the development of the halal industry is not only understood as fulfilling religious aspects but also encompasses increasingly significant economic, social, and global dimensions. The halal industry plays a crucial role in creating added value, expanding employment opportunities, and enhancing the competitiveness of national products in the international market. This article aims to comprehensively examine the halal industry development strategy in Indonesia by examining the concept of the halal industry, its current conditions and potential, the role of digitalization in expanding market access, applicable regulations, and various challenges and recommendations for its development. The research method used is a qualitative approach through literature review utilizing relevant and up-to-date scientific sources. The study results indicate that Indonesia has significant potential to become a global halal industry hub, supported by a large domestic market, abundant natural resources, and rapid development of digital technology. However, the development of the halal industry still faces various challenges, such as limited product competitiveness, suboptimal regulatory implementation, and a lack of human resource readiness. Therefore, an integrated and sustainable development strategy is needed so that the Indonesian halal industry can compete at the national and global levels.